Trophic Transfer of Single-Walled Carbon Nanotubes at the Base of the Food Chain and Toxicological Response - Majed Al-Shaeri; Lynn Paterson; Margret Stobie; Paul Cyphus; Mark G. J. Hartl (Nanomaterials, 2022)
The potential for trophic transfer of single-walled carbon nanotubes (SWCNTs) was assessed using the green algae Tetraselmis suecica and the blue mussel Mytilus edulis in a series of laboratory experiments. Swanee River Natural Organic Matter (SRNOM)-dispersed SWCNTs were introduced into growing algal cultures. Light microscopical observations, confirmed by scanning electronic microscopy (SEM) and Raman spectroscopy, showed that SWCNT agglomerates adhered to the external algal cell walls and transmission electronic microscopy (TEM) results suggested internalization. A direct effect of SWCNT exposure on the algae was a significant decrease in growth, expressed as chlorophyll a concentration and cell viability. Mussels, fed with algae in the presence of SWCNTs, led to significantly increased pseudofaeces production, indicating selective feeding. Nevertheless, histological sections of the mussel digestive gland following exposure showed evidence of SWCNT-containing algae. Furthermore, DNA damage and oxidative stress biomarker responses in the mussel haemocytes and gill tissue were significantly altered from baseline values and were consistent with previously observed responses to SWCNT exposure. In conclusion, the observed SWCNT-algal interaction demonstrated the potential for SWCNT entrance at the base of the food chain, which may facilitate their trophic transfer with potential consequences for human exposure and health.